Anti-ulcerogenic effect of KFP-H008 against ethanol-induced gastric ulcer via p38 MAPK/NF-κB pathway. Issue 78 (23rd October 2017) - Su, Mei; Li, Cheng-yuan; Zhou, Lin; Yan, Yun-yi; Ao, Lu-yao; Wang, Guang-ji; Fang, Wei-rong; Li, Yun-man
Abstract : KFP-H008, a novel potassium-competitive acid blocker developed for the treatment of acid-related diseases, has been reported to inhibit gastric acid secretion effectively, while its effects on gastric ulcer have not been previously explored. Abstract : 1-(5-(1 H -Indol-5-yl)-1-(pyridin-3-ylsulfonyl)-1 H -pyrrol-3-yl)- N -methylmethanamine (KFP-H008), a novel potassium-competitive acid blocker developed for the treatment of acid-related diseases, has been reported to inhibit gastric acid secretion effectively, while its effects on gastric ulcer have not been previously explored. The current study aimed to investigate the protective potential of KFP-H008 on ethanol-induced gastric ulcer and gastric epithelial cell damage. 0.2 ml absolute ethanol and 5% ethanol were applied to establish a gastric ulcer model in vivo and in vitro, respectively. In vivo, pre-treatment with KFP-H008 reduced ethanol-induced gastric ulcer index (gross lesions) and histopathological scores (microscopic lesions), and also decreased the expressions of malonaldehyde (MDA), NO and myeloperoxidase (MPO), along with the decline of pro-inflammatory cytokines (TNF-α, IL-1β and IL-6) or iNOS in tissues and serum. Meanwhile, the levels of superoxide dismutase (SOD) and glutathione (GSH) were both increased. Pre-treatment with KFP-H008 also effectively down-regulated the protein expression of p-p38 mitogen-activated protein kinase (MAPK) and p65 nuclear factor-κB (NF-κB) in ethanol-treated gastric tissues. In vitro, pre-treatment of KFP-H008 promoted the cell viability after challenge of 5% ethanol, and suppressed the expression of TNF-α, IL-1β, IL-6 or iNOS in cell supernatant. Furthermore, the activations of p38 MAPK and NF-κB in GES-1 cells induced by ethanol were reversed by KFP-H008. In all, KFP-H008 presented protective effects against gastric ulcer and the underlying mechanism might be associated with the antioxidant properties and anti-inflammatory status through p38 MAPK/NF-κB pathway.